The relationship between exposure to film, television and social media and the attitude of call center agents in Iloilo City towards infidelity and live-in partnership - Landas, Marie Bjorn M.; Salvaleon, Charlotte Antoinnette P. (2015.)
This research is a descriptive survey using correlation. It has the intention of defining the respondents? media usage and marital values. And to find out the relationship between these two variables. The data analysis tool is used in the research is Descriptive Statistics in order to check the frequencies and percentage of the respondents answers. The researcher will first find out the level of exposure of the respondents to each type of media (film, social media and television) by using the frequency of the descriptive statistics, the researcher will then find out which type of media the respondents are highly exposed to and so on. From the analyzed data, this was able to determine that there was no relationship between the call center agent?s level of exposure to media and his attitude towards infidelity and live-in partnership. There is no significance of the phenomenon in the respondents used in the study. This study would be beneficial to future researchers who are interested in creating a study with a similar structure and topic with the study may also benefit. This study deeply involves the current trend in Philippine media.
Thesis -- Bachelor of Arts in Communication and Media Studies. University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Call center; Infidelity; Live-in Partnership; Media; Extra-Marital Affair; Marriage